The two waves of financial liberalization in Latin America - Frenkel, Roberto (2001)
This paper draws on Roberto Frenkel (1998), ôCapital Market Liberalization and Economic Performance in Latin Americaö, Working Paper Series III, Working Paper Nª1, CEPA, New School University. The authors are grateful to two anonymous referees for their helpful comments